Different in vitro metabolism of paclitaxel and docetaxel in humans, rats, pigs, and minipigs - Vaclavikova, Radka; Soucek, Pavel; Svobodova, Lenka; Anzenbacher, Pavel; Simek, Petr; Guengerich, F Peter; Gut, Ivan (Drug metabolism and disposition: the biological fate of chemicals, 2004)
We investigated cytochrome P450 (P450)-catalyzed metabolism of the important cancer drugs paclitaxel and docetaxel in rat, pig, minipig, and human liver microsomes and cDNA-expressed P450 enzymes. In rat microsomes, paclitaxel was metabolized mainly to C3'-hydroxypaclitaxel (C3'-OHP) and to a lesser extent to C2-hydroxypaclitaxel (C2-OHP), di-hydroxypaclitaxel (di-OHP), and another unknown monohydroxylated paclitaxel. In pig and minipig microsomes, this unknown hydroxypaclitaxel was the main metabolite, whereas C3'-OHP was a minor product. In minipigs, C2-OHP was the next minor product. In human liver microsomes, 6 alpha-hydroxypaclitaxel (6 alpha-OHP) was the main metabolite, followed by C3'-OHP and C2-OHP. Among different cDNA-expressed human P450 enzymes (CYP1A2, 1B1, 2A6, 2C9, 2E1, and 3A4), only CYP3A4 enzyme formed C3'-OHP and C2-OHP. Docetaxel was metabolized in pig, minipig, rat, and human liver microsomes mainly to hydroxydocetaxel (OHDTX), whereas CYP3A-induced rat microsomes produced primarily diastereomeric hydroxyoxazolidinones. Human liver microsomes from 10 different individuals formed OHDTX at different rates correlated with CYP3A4 content. Troleandomycin as a selective inhibitor of CYP3A inhibited the formation of C3'-OHP, C2-OHP, and di-OHP, as well as the unknown OHP produced in rat, minipig, and pig microsomes. In human liver microsomes, troleandomycin inhibited C3'-OHP and C2-OHP formation, and a suitable inhibitor of human CYP2C8, fisetin, strongly inhibited the formation of 6 alpha-OHP, known to be catalyzed by human CYP2C8. In conclusion, the metabolism of docetaxel is the same in all four species, but metabolism of paclitaxel is different, and 6 alpha-OHP remains a uniquely human metabolite. Pigs and minipigs compared with each other formed the same metabolites of paclitaxel.
Keywords: dospělí; flavonoidy; Animals; Swine, Miniature; Rats; Kinetics; docetaxel; Troleandomycin; Rats, Wistar; Adult; Flavonoids; In Vitro Techniques; druhová specificita; Adolescent; fytogenní protinádorové látky; Enzyme Inhibitors; techniky in vitro; lidé; miniaturní prasata; Species Specificity; prasata; Docetaxel; Cytochrome P-450 Enzyme System; Taxoids; jaterní mikrozomy; Flavonols; Paclitaxel; Antineoplastic Agents, Phytogenic; Male; Swine; mladiství; inhibitory enzymů; paclitaxel; systém (enzymů) cytochromů P-450; flavonoly; Microsomes, Liver; krysa rodu Rattus; troleandomycin; Isoenzymes; zvířata; mužské pohlaví; taxoidy; kinetika; izoenzymy; potkani Wistar; Humans